Internet as a tool to access high-risk men who have sex with men from a resource-constrained setting: a study from Peru. Issue 7 (11th October 2007) - Blas, M M; Alva, I E; Cabello, R; Garcia, P J; Carcamo, C; Redmon, M; Kimball, A M; Ryan, R; Kurth, A E
Abstract : Objectives: In Peru, current interventions in high-risk men who have sex with men (MSM) reach a limited number of this population because they rely solely on peer education. The objective of this study was to assess the use of the internet as an alternative tool to access this population. Methods: Two nearly identical banner ads—both advertising an online survey but only one offering free HIV/syphilis tests and condoms—were displayed randomly on a Peruvian gay website. Results: The inclusion of the health incentive increased the frequency of completed surveys (5.8% vs 3.4% of delivered impressions; p<0.001), attracting high-risk MSM not previously tested for HIV but interested in a wide variety of preventive Web-based interventions. Eleven per cent (80/713) of participants who said they had completed the survey offering free testing visited our clinic: of those who attended, 6% had already been diagnosed as having HIV, while 5% tested positive for HIV. In addition, 8% tested positive for syphilis. Conclusions: The internet can be used as a tool to access MSM in Peru. The compensation of a free HIV/syphilis test increased the frequency of participation in our online survey, indicating that such incentives may be an effective means of reaching this population. However, as only a small percentage of participants actually reported for testing, future research should develop and assess tailored internet interventions to increase HIV/STI testing and delivery of other prevention services to Peruvian MSM.